New insights on mucormycosis and its association with the COVID-19 pandemic - Mona G Alshahawey; Ghadir S El-Housseiny; Noha S Elsayed; Mohammad Y Alshahrani; Lamia M EL Wakeel; Khaled M Aboshanab (Future Science OA)
COVID-19 continues to cause significant fatality worldwide. Glucocorticoids prove to play essential roles in COVID-19 management; however, the extensive use of steroids together with the virus immune dysregulation may increase the danger of secondary infections with mucormycosis, an angioinvasive fungal infection. Unfortunately, a definite correlation between COVID-19 and elevated mucormycosis infection cases is now clear worldwide. In this review, we discuss the historical record and epidemiology of mucormycosis as well as pathogenesis and associated host immune response, risk factors, clinical presentation, diagnosis and treatment. Special emphasis is given to its association with the current COVID-19 pandemic, including latest updates on COVID-19-associated mucormycosis cases globally, with recommendations for efficacious management.